Sustainable Engineering Proceedings of EGRWSE 2018 - Agnihotri, Arvind Kumar; Reddy, Krishna; Bansal, Ajay (Lecture Notes in Civil Engineering,, 2019)
This volume contains selected papers presented during the International Conference on Environmental Geotechnology, Recycled Waste Material and Sustainable Engineering (EGRWSE-2018). The multidisciplinary articles in this volume discuss environment-friendly technologies and the application of 'smart' solutions and initiatives to improve infrastructure and services, with a strong emphasis on sustainability and conservation of resources. This volume will be of interest to engineers, professionals, and researchers working on improving urban infrastructure and strengthen civic amenities in a sustainable manner. .